SOSIALISASI DAN PENDAMPINGAN MASYARAKAT DALAM MEMAJUKAN EKOWISATA PANTAI BATU BURUNG KOTA SINGKAWANG KALIMANTAN BARAT - Satyahadewi, Neva (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2023)
Pantai Batu Burung Singkawang is one of the tourist destinations that is visited by local tourists from the Singkawang and surrounding areas, especially on Sundays and school holidays or Eid holidays. With the characteristic distribution of granite along the coast, it adds to the natural beauty of the beach. The Community Service Activities (PKM) which are carried out in September-November in the area aim to advance Pantai Batu Burung tourism through assisting the local community in terms of maintaining the cleanliness of the beach including the tidiness and order of the street vendors, being friendly to visitors and promoting the beauty of ecotourism Pantai Batu Burung through social media. This activity was attended by 20 residents of the Sedau Village community, 15 of whom were culinary business owners in the coastal area. Based on the evaluation and monitoring during the activity, it shows that the business community on this beach has carried out a beach cleaning program regularly so that the beach and its surroundings always look clean, always maintain hospitality to visitors and have participated in promoting the Pantai Batu Burung tourist destination through social media with share beach profile videos and infographics.Keywords : Pantai Batu Burung, ecotourism, granite, infographics, Sedau